2003
DOI: 10.1021/ed080p346
|View full text |Cite
|
Sign up to set email alerts
|

Learning in Chemistry with Virtual Laboratories

Abstract: Using an interactive software program, Virtual Chemistry Laboratory (VCL), we conducted an educational experiment to assess the software's influence on student understanding of some basic organic chemistry laboratory techniques. First-year engineering students at the Superior Polytechnic School of Córdoba were evaluated: more favorable results were obtained from students who had worked with the VCL when compared to results of students who had not worked with the VCL. We conclude that the use of VCL helps stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 21 publications
(26 reference statements)
0
28
0
7
Order By: Relevance
“…The results indicated that this combination assisted in the performance improvement in hands-on laboratory and that could contribute to the improvement of student learning. Another study in chemistry field adopted the combinational use of virtual laboratory and traditional laboratory experiments (Martinez-Jiménez et al, 2003). The study concluded that the blended educational approach facilitated the reflective self-training of students, helped to eliminate the overcrowding problem in campus-on sessions and finally contributed to the effective use of time from educators, as they focused on explanation of theory, since less time was spent to laboratory instrument operation and experimental procedures.…”
Section: Blended Usage Approachmentioning
confidence: 99%
“…The results indicated that this combination assisted in the performance improvement in hands-on laboratory and that could contribute to the improvement of student learning. Another study in chemistry field adopted the combinational use of virtual laboratory and traditional laboratory experiments (Martinez-Jiménez et al, 2003). The study concluded that the blended educational approach facilitated the reflective self-training of students, helped to eliminate the overcrowding problem in campus-on sessions and finally contributed to the effective use of time from educators, as they focused on explanation of theory, since less time was spent to laboratory instrument operation and experimental procedures.…”
Section: Blended Usage Approachmentioning
confidence: 99%
“…Researchers have emphasized that performing practical experimentation within a virtual laboratory significantly enhances the student's academic achievement, fosters motivation towards the course, and provides perception of abstract scientific concepts [5], [9][10][11].…”
Section: Related Workmentioning
confidence: 99%
“…Su uso presenta muchas ventajas (Bortnik, 2017;Chan, 2009;Climent-Bellido, 2003;Cobb, 2009;De Jong, 2013;Franco, 2013; García Armada, 2016;Heradio, 2016;Jensen, 2013): fomentan el trabajo en equipo, son motivantes, implican menos costes que los laboratorios tradicionales, fomentan la creatividad y un aprendizaje más autónomo, se pueden repetir las experiencias tantas veces como sea necesario, disminuyen el miedo al error y al fracaso por parte del discente, facilitan la visualización de procesos y conceptos abstractos, y permiten al docente llevar a cabo actividades de laboratorio sin tener que cambiar de aula. Además, ofrecen alternativas para la enseñanza híbrida y a distancia.…”
Section: Introductionunclassified
“…Su uso presenta muchas ventajas (Bortnik, 2017;Chan, 2009;Climent-Bellido, 2003;Cobb, 2009;De Jong, 2013;Franco, 2013; García Armada, 2016;Heradio, 2016;Jensen, 2013): fomentan el trabajo en equipo, son motivantes, implican menos costes que los laboratorios tradicionales, fomentan la creatividad y un aprendizaje más autónomo, se pueden repetir las experiencias tantas veces como sea necesario, disminuyen el miedo al error y al fracaso por parte del discente, facilitan la visualización de procesos y conceptos abstractos, y permiten al docente llevar a cabo actividades de laboratorio sin tener que cambiar de aula. Además, ofrecen alternativas para la enseñanza híbrida y a distancia.El impacto de los laboratorios virtuales, y la disyuntiva entre experimentos tradicionales y virtuales, han sido objeto de un considerable interés por parte de la comunidad educativa en los últimos años en diferentes áreas de conocimiento: Física (Deutsch, 2014;Finkelstein, 2005;Franco, 2013;Wieman, 2008), Química (Bortnik, 2017;Climent-Bellido, 2003; García Armada, 2016;Jensen, 2013;Moore, 2014; Tatli, 2010), Biología y Ciencias de la Vida (Lewis, 2014;Sanz, 2005;Stuckey-Mickell, 2007) e Ingeniería (Chan, 2009;Heradio, 2016;Ma, 2006;Potkonjak, 2016).En general, diferentes estudios, tanto de Ciencias Experimentales como de Ciencias de la Salud, muestran niveles similares de éxito con ambos enfoques en cuanto a calificaciones, adquisición de contenidos y/o valoración (Cobb, 2009;Darrah, 2014;De Jong, 2013;Hawkins, 2013;Klar, 2007;Lewis, 2014;Makransky, 2016;Pyatt, 2012; Spernjak, 2017;Triona, 2003;Tsihouridis, 2013;Winkelmann, 2014;…”
unclassified